IMPELEMENTASI TEKNOLOGI DIGITAL DALAM PENGEMBANGAN METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL-CHASANAH JAKARTA - Ayu Ningrum, Desy; Chotimah, Husnul; Sopha Karim, Nala (LP2M JAMIAT KHEIR, 2025)
The development of digital technology has brought significant changes in various fields, including education. One of its impacts can be seen in the increasingly diverse and interactive learning methods. This study aims to examine the role of digital technology in the development of learning methods for Islamic Religious Education (IRE) in Grade 10 at SMA Al-Chasanah Jakarta. This research uses a qualitative approach with a case study method. Data were collected through student observation. The results of the study show that the use of digital technology—such as presentation media, educational videos, and interactive quiz applications—can increase students' learning interest and help teachers deliver complex material more effectively. With adequate support, the application of digital technology can be an innovative solution to improve the quality of Islamic education in secondary schools. Therefore, continuous training for teachers and the provision of technological infrastructure that supports the learning process are essential.